Pengaruh Digital Marketing, Cita Rasa, Dan Potongan Harga Terhadap Minat Beli Produk Minuman Boba Di Rantauprapat - Widya Prasetya; Bayu Eko Broto; Elida Florentina Sinaga Simanjorang (Jurnal Mirai Management, 2023)
The purpose of this study was to determine the effect of digital marketing, taste, and price discounts on the intention to buy Boba beverage products in Rantauprapat, Labuhanbatu Regency. This type of research uses a quantitative descriptive method. The population of this study were all consumers in the city of Rantauprapat, North Rantau and South Rantau districts, Labuhanbatu district, North Sumatra. And for the sample, there are 100 people who are derived from the Wibisono formula. The data obtained is primary data which is the result of respondents' answers or questionnaires distributed. The results of the t test show that Digital Marketing (X1) has a very significant effect on purchase intention. It can be seen from the results of tcount > ttable (3.199 > 1.984) with a significance value of 0.002 ttable (4,416 > 1,984) with a significance value of 0.000 ttable (3.611 > 1.984) with a significance value of 0.001